Filosofis Equilibrasi dalam Konsep Pendidikan Islam Relevansinya Bagi Akselerasi Pengembangan Nilai Kepribadian dalam Konteks Ke-Indonesiaan - Wahyudin Wahyudin; Nurul Mahmudah; Dedi Wahyudi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
This article depicts the philosophical equilibration in the concept of Islamic education refers to the basic principle of perfect human beings who aim to get happiness in the life of the world and the hereafter. The goal is the concept of Islam to teach a balance between individuals, social, physical, and spiritual, with the hope that there will be no imbalances in the life of the nation and state. The research used the dynamic personality development theory, supported by theories of individual and social balancing processes and inspired by the concept of Islamic education. This study describes human experience and presents a philosophical view of life about the value of personality in the life of the nation and state. The research results showed that the philosophical acceleration of the development of the value of Personality in people's lives, by means of a persuasive approach as a force that serves to bring every citizen closer to life in society.